2016
DOI: 10.1021/acs.jpcb.6b04052
|View full text |Cite
|
Sign up to set email alerts
|

N3 Protonation Induces Base Rotation of 2′-Deoxyadenosine-5′-monophosphate and Adenosine-5′-monophosphate

Abstract: Infrared multiple photon dissociation (IRMPD) action spectroscopy experiments combined with theoretical calculations are performed to investigate the stable gas-phase conformations of the protonated adenine mononucleotides, [pdAdo+H](+) and [pAdo+H](+). Conformations that are present in the experiments are elucidated via comparative analyses of the experimental IRMPD spectra and the B3LYP/6-311+G(d,p) IR spectra predicted for the conformers optimized at this level of theory. N3 protonation is preferred as it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 50 publications
3
33
0
Order By: Relevance
“…The effect of adenosine residues on the yield of c and y fragments from CAD of gaseous RNA (M+nH) n+ ions observed here, and the lack of it when A is replaced by c 3 A or c 1,3 A but not c 1 A or c 7 A (Figures 3 and 4), implies adenine protonation at N3, in agreement with data from hydrogen/deuterium exchange (51) and a combined experimental and theoretical study of adenosine-5′-monophosphoric acid (M+H) + ions (52). The increased proton affinity of N3 over that of N1 and N7 in adenosine-5′-monophosphoric acid (M+H) + ions results from stabilization (by >35 kJ/mol) of a syn , C2′-endo conformation in which the protonated N3 forms an ionic hydrogen bond with a nonbridging oxygen of the uncharged monophosphoester moiety (N3H + ···O = P motif) (52). This is the very same motif that we hold responsible for facilitating nucleophilic attack of the 2′-OH group on the phosphorus in the course of phosphodiester backbone bond cleavage by CAD of (M+nH) n+ ions of RNA (Scheme 2), although we cannot exclude the possibility of ionic hydrogen bonding to a bridging instead of a non-bridging oxygen of the uncharged phosphodiester moiety.…”
Section: Resultssupporting
confidence: 87%
“…The effect of adenosine residues on the yield of c and y fragments from CAD of gaseous RNA (M+nH) n+ ions observed here, and the lack of it when A is replaced by c 3 A or c 1,3 A but not c 1 A or c 7 A (Figures 3 and 4), implies adenine protonation at N3, in agreement with data from hydrogen/deuterium exchange (51) and a combined experimental and theoretical study of adenosine-5′-monophosphoric acid (M+H) + ions (52). The increased proton affinity of N3 over that of N1 and N7 in adenosine-5′-monophosphoric acid (M+H) + ions results from stabilization (by >35 kJ/mol) of a syn , C2′-endo conformation in which the protonated N3 forms an ionic hydrogen bond with a nonbridging oxygen of the uncharged monophosphoester moiety (N3H + ···O = P motif) (52). This is the very same motif that we hold responsible for facilitating nucleophilic attack of the 2′-OH group on the phosphorus in the course of phosphodiester backbone bond cleavage by CAD of (M+nH) n+ ions of RNA (Scheme 2), although we cannot exclude the possibility of ionic hydrogen bonding to a bridging instead of a non-bridging oxygen of the uncharged phosphodiester moiety.…”
Section: Resultssupporting
confidence: 87%
“…Interestingly, although it is commonly held that the N3 site of adenine is not favored for electrophilic attack on adenine 11 , there is ample recent evidence made by IRMPD action spectroscopy showing that the N3 position is in fact favored in the protonation and alkali metal cation attachment of both the free base and adenine 9 DNA and RNA nucleosides [59][60][61] and nucleotides. 39 Also UVPD 62 and IRMPD 63 spectroscopy of alkali metal cation-adenine complexes and their hydrated forms confirm that N3 binding is preferred in a bidentate fashion with the N9 position on the tautomer A7 and support the view that N3 attack has likely been unduly undervalued.…”
Section: Resultsmentioning
confidence: 74%
“…This differs from that found for the protonated cytosine and guanine nucleosides, where N-glycosidic bond cleavage occurs via two different TSs, TS 1 and TS n (where TS n lies lower in energy than TS 1 ). 34,47,75 Our previous IRMPD study of [dAdo+H] + and [Ado+H] + determined that both N3 and N1 protonated conformers may coexist in the gas phase. This explains the very similar apparent thresholds observed for the two primary CID channels of [Ado+H] + .…”
Section: Effects Of the 2 0 -Hydroxyl Substituent On N-glycosidic Bonmentioning
confidence: 99%
“…34,[43][44][45][46][47][48] In particular, the IRMPD study of [dAdo+H] + and [Ado+H] + found that the presence of the sugar moieties alters the preferred site of protonation to N3 from that of the isolated adenine nucleobase, N1. Recently, we examined the gas-phase conformations and energetics of a series of protonated DNA and RNA nucleosides and nucleotides using IRMPD action spectroscopy and electronic structure calculations.…”
Section: Introductionmentioning
confidence: 99%